Dale Knickerbocker, editor. Lingua Cosmica: Science Fiction From Around the World. U of Illinois P, 2018. - Jeremy Glazier (Studies in 20th & 21st Century Literature, 2019)
Review of Dale Knickerbocker, editor. Lingua Cosmica: Science Fiction From Around the World. U of Illinois P, 2018.
Keywords: Science Fiction; sf; Dale Knickerbocker; Liu Cixin; Angélica Gorodischer; Jacek Dukaj; Jean-Claude Dunyach; Boris Strugatsky; Arkady Strugatsky